Performance improvement of direct torque controlled five‐phase induction motor in context of common‐mode voltage, torque ripple and demagnetisation under low speed region. Issue 4 (1st March 2020) - Tatte, Yogesh; Aware, Mohan; Kumar Singh, Ankit
Abstract : This study focuses on the performance improvement of direct torque controlled (DTC) five‐phase induction motor (FPIM). The performance indices are common‐mode voltage (CMV), torque ripple and demagnetisation during low‐speed operation. The three‐level five‐phase inverter (TL‐FPI) is used for feeding the FPIM, since more voltage vectors are available in TL‐FPI than its two‐level counterpart. Among available 243 voltage vectors, 41 non‐vertex voltage vectors are employed. These 41 voltage vectors through seven‐level torque comparator (SLTC) fires an inverter. The SLTC reduces the torque ripple. All the employed 41 voltage vectors have zero CMV output. The voltage vectors are selected so that the magnitude of radial component of the resultant stator flux under low‐speed operation is more than the same under normal speed operation. This modification resolves the problem of demagnetisation during low‐speed operation. The proposed method achieves the intended targets without losing simplicity and dynamics of the classical DTC method. The performance improvement of the five‐phase machine is validated through several results.